Naftidrofuryl-induced acute hepatic necrosis. Issue 726 (April 1986) - de Caestecker, J. S.; Heading, R. C.
Abstract : Acute hepatic necrosis is described in a 60 year old woman treated with naftidrofuryl for 5 months.